“Are the Core Competencies of Cosmic Solutions sufficiently dynamic to enable the firm’s strategic vision?” - Leach, David (2010)
Hamel and Prahalad (1990) state core competences are the ‘collective learning in the organisation’ and that they are the result of ‘complex harmonisation of individual technologies and production skills.’ However, this is a point in time assessment and sustained strategic advantage is gained from an ability to evolve over time, Teece et al, (1997) state ‘the firm’s ability to integrate, build, and reconfigure internal and external competences to address rapidly changing environments’ is key for sustained strategic advantage - they call this dynamic capabilities.